The Influence of the Examples Non-Examples Learning Model on the Learning Outcomes of PKn Students of SMK PAB 3 Medan Estate - Chairunnisa, Vinda (Pancasila and Civics Education Journal (PCEJ), 2022)
Learning is basically the provision of knowledge given to students by students, using various models, strategies and methods in learning, not forgetting to also pay attention to students' psychological factors. Data were collected by means of observation and interviews, questionnaires, documentation and triangulation. This study aims to determine the influence of the examples non-examples learning model on student learning outcomes in civic education subjects, as well as to find out how much influence the non-examples learning model has on pkn learning outcomes with human rights material in class X AK SMK PAB 3 Medan Estate. The samples used in this study were all class X AK students of SMK PAB 3 Medan Estate, totaling 35 people. From the data obtained by researchers, it can be concluded that there is an effect of examples non examples (X) learning on student learning outcomes (Y) material at the level of